Development of a model of of energy efficient hybrid engine towards green technology - Rahman, Mohammed Ataur (Inderscience Enterprises Ltd., 2011)
The main focus of this study is to develop a fuel efficient hybrid engine to operate a designed and developed urban car of weight 1.42 kN. The hybrid engine is developed by coupling a high efficient 12 volt generator with a 33.5 cc engine of power 1.18 kW @7,000 rpm. The generator starts to power the DC motor to propel the car as soon as the engine is started. The engine optimum speed is considered to be 4,000 rpm to operate the generator to power the DC motor for propelling the car on 0% slope. While, it is operated at 6,000 rpm to power the vehicle on 20% slope. Two super-capacitors each of 2 Farad are equipped in parallel with the generator in order to maintain the constant power supply to the DC motors for propelling the car with speed of 35 km/h. The hybrid engine was run at 65% efficiency which is more efficient than the conventional IC engine. The energy efficient hybrid engine cut carbon dioxide (CO2) and nitrogen oxides (N2O) emission significantly.